Dual role of TGF-β in early pregnancy: clues from tumor progression. Issue 6 (17th February 2019) - Latifi, Zeinab; Nejabati, Hamid Reza; Abroon, Sina; Mihanfar, Aynaz; Farzadi, Laya; Hakimi, Parvin; Hajipour, Hamed; Nouri, Mohammad; Fattahi, Amir
Abstract: TGF-β signaling in the endometrium is active during the implantation period and has a pivotal role in regulating endometrial receptivity and embryo implantation. During embryo implantation, both apoptosis and proliferation of endometrial cells happen at the same time and it seems TGF-β is the factor that controls both of these processes. As shown in cancer cells, in special conditions this cytokine can have a dual effect and switch the action from apoptosis to proliferation. Owing to the similarity between embryo implantation and cancer development and also unusual pattern of proliferation and remodeling in the uterus, in this review we suggest the existence of such a switching in endometrium during the early pregnancy. Moreover, we address some potential mechanisms that could regulate the switching. A better understanding of the molecular mechanisms regulating TGF-β action and signaling during the implantation period could pave the way for introducing novel therapeutic strategies in order to solve implantation-associated issues such as repeated implantation failure. Abstract : TGF-β has a dual effect in tumor progression and can switch the cell fate from apoptosis to proliferation, and possibly plays a similar role in endometrium during the early pregnancy.